Vitamina D3 (1,25(OH)2D3) em sua forma ativa reduz alterações pulmonares inflamatórias e funcional secundária a pancreatite aguda alcoólica em camundongos swiss - Ribeiro, Thiago Andrade (2024)
Acute pancreatitis (AP) triggers systemic inflammatory response syndrome, in which 60% of individuals develop acute lung injury (ALI) and consequently acute respiratory distress syndrome (ARDS), the pathogenesis of which is not fully understood. Vitamin D3 has therapeutic activity and is used in the treatment of ALI. Therefore, the present study sought to use the active form of vitamin D3 as a possible anti-inflammatory agent in ALI resulting from experimental alcoholic AP. Swiss mice were used and distributed into 6 experimental groups: Saline; EtOH/POA; and EtOH/POA + vitamin D3 at doses of 0.3, 1, 3, and 30 µg/kg orally. After induction of AP, the animals were anesthetized for spirometry analysis and then euthanized for blood collection and measurement of α-amylase and lipase, collection of bronchoalveolar lavage (BAL) for total and differential leukocyte counts, and removal of the pancreas and lung for histopathological analysis of myeloperoxidase (MPO) and reduced glutathione (GSH). The data obtained highlighted the ability of vitamin D3 to reduce (p<0.05) the infiltration of nuclear polymorphs and alveolar thickening in lung histological scores at all doses tested, except at 0.3 µg/kg when compared to the EtOH/POA group. As well as reduced levels (p<0.05) of α-amylase at doses of 0.3, 1 and 3 µg/kg and for lipase, with reduction (p<0.05) at doses of 0.3, 1, 3 and 30 µg/kg when compared to the EtOH/POA group. MPO activity was also reduced (p<0.05) in lung tissue at doses of 0.3, 1, 3 and 30 µg/kg when compared to the EtOH/POA group. Lung GSH analyses showed an increase (p<0.05) at doses of 0.3, 1, 3 and 30 µg/kg when compared to the EtOH/POA group. The number of total leukocytes in BAL showed a reduction (p<0.05) at doses of 1, 3 and 30 µg/kg, as well as the number of macrophages with vitamin D3 treatment at doses of 0.3, 1, 3 and 30 µg/kg when compared to the EtOH/POA group (p<0.05). Based on the results, the dose of 1 µg/kg of vitamin D3 was chosen to continue the cytokine and spirometry analyses. Regarding cytokines, vitamin D3 was able to reduce the amount of NFκB and IL-1β proteins when compared to the EtOH/POA group (p<0.05), while spirometry indicated an increase (p<0.05) in respiratory flow and respiratory rate when compared to the EtOH/POA group. Therefore, it was possible to observe the therapeutic activity of vitamin D3 in ALI caused by alcoholic PA, by reducing levels of pancreatic enzymes, inflammatory and oxidative processes and functional damage.